Bedding material in dirt-floor pens reduces heat - Rezac, D.J.; Thomson, Daniel U.; Reinhardt, Christopher D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2012)
Weather-related stressors are a well-recognized opponent to animal welfare and can have important ramifications for animal performance. Sound animal husbandry practices historically have attempted to diminish the effects of deleterious environmental factors. Providing aid to animals when temperatures are above or below their thermal neutral zone (TNZ) can improve animal welfare and/or performance. Because most breeds of cattle are not well equipped to deal with heat, the temperatures at which heat stress can begin to affect cattle can be surprisingly low. The onset of mild heat stress can occur at a temperature humidity index (THI1) value of 75, which can correspond to an ambient temperature as low as 78°F. Aside from food, water, and shelter, arguably the most widely used intervention to counteract the elements is the provision of bedding material during times of cold weather or during events for which the stress of cold may prove too difficult for animals to compensate (i.e., calving, illness, etc.). By providing a layer of insulation as bedding for animals, heat exchange via conduction from their body to the earth is decreased, allowing them to maintain body temperature at a much lower cost to their metabolism. This basic principle of insulation also may be applied in times of heat stress. In an attempt to decrease the effects of heat stress in feedlot cattle, some producers apply wheat straw or grass hay as bedding material, hypothesizing that bedding acts as an insulator from the pen floor, which otherwise serves as a reservoir and conductor of heat. Bedding materials normally are lighter in color than the pen surface, and therefore have less solar heat gain. To the best of our knowledge, no studies have been conducted to examine the effects of these bedding materials on the temperature of the pen surface. Additionally, determining the effects of varying thicknesses of manure on pen surface temperatures may provide useful information for management decisions regarding pen cleaning and maintenance.
Keywords: Beef; Bedding material; Insulation; Heat stress